Conversations in Social Distancing: Breakdown and Repair - Niño Rey Otara; Ethel S. Doria; Jay L. Galimpin (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study aimed to know the conversational breakdown during the pandemic in the context of social distancing, how it is repaired and what are the barriers that cause the communication breakdown. This is a qualitative research design through the phenomenology approach. This is conducted through extensive focusing and observation of the researchers on the lived communication processes during the pandemic. The study was conducted in the respective barangays, namely: Abihilan of Candijay, Guinacot and Mayuga of Guindulman, Botoc Oriental of Loay, and Hinlayagan Ilaud of Trinidad in the Province of Bohol. The result of the study shows that communication breakdown in instances where there are gatherings, business transactions, and interpersonal conversations. The interlocutor finds ways to repair the breakdown, like repeating their response, modifying their answers by adding and subtracting words or phrases, and recasting. These repair strategies can be done through verbal and non-verbal responses. Based on the findings and conclusions drawn, the researchers were able to make recommendations such as: suggest vendors to put pricelist or any visual attractive communication of the goods that they sell, propose to the Sangguniang Barangay plans for accessibility guidelines like acoustic or visual accessibility guidelines in the public offices or in any of the public spaces, modify the use of hand signals as an awareness disasters and calamities and safety purposes and lastly, future researchers may look at other scenarios where breakdown usually happens and find out strategies of repair in the context of during and post pandemic, election campaign period,